Formation of productivity and quality of durum spring wheat depending on a mineral nutrition in the Right-Bank Forest-Steppe of Ukraine - Каленська, С. М.; Шутий, О. І. (Scientific Progress & Innovations, 2016)
The influence of variety features of mineral feed of the durum spring wheat in Right-Bank Forest-Steppe of Ukraine. It has been established that the use of foliar top-dressing on the background of the main fertilizer has a positive effect on performance and quality of the investigated varieties. We substantiated the role of plant nutrition system that allows you to manage the formation of grain productivity crop of durum spring wheat. We optimized power mode which provides a more complete disclosure of the resource potential of the plants thereby crop yield increases.